Neoliberal Governance in the Philippines: Ideational Policy Reform in the Ramos Administration, 1992-1998 - Garcia, Robin Michael U. (Philippine Journal of Public Administration; Vol 56 No 2 (2012), 2017)
Neoliberalism in the Philippines came at a time when the country was considered the “Sick Man of Asia” and during the immediate decade of the post-Cold War. This article provides a partial explanation why more neoliberal forms of governance were adopted during the Ramos Administration. Using an ideational approach in the political economy of public policy and governance reforms, the article traces how neoliberal governance gained acceptance in the Philippines. It argues that through a three-level reform process, the confluence of exogenous and endogenous factors, as well as the “epistemic privileged” status of neoliberalism during that time led to the demise of the Keynesian state-led governance model and the eventual acceptance of the market-led neoliberal governance model.
Keywords: governance, neoliberalism, ideational framework, Ramos administration, Keynesian governance, epistemic privilege